The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/petr.14102
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric KT in children up to 15 kg: A single‐center experience

Abstract: Background KT is the preferred treatment for ESRD in pediatrics. However, it may be challenging in those weighing ≤15 kg with potential complications that impact on morbidity and graft loss. Methods This retrospective review reports our experience in KT in children, weighing ≤15 kg, and the strategies to reduce morbidity and mortality. Results All patients were on RRT prior to KT. Patients reached ESRD mainly due to urologic malformations (54.54%). LD was performed in 82% of patients. The recipient's median ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Finally, a total of 23 studies were included in this systematic review (Fig. 1) [9][10][11]12,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Search Resultsmentioning
confidence: 99%
“…Finally, a total of 23 studies were included in this systematic review (Fig. 1) [9][10][11]12,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Search Resultsmentioning
confidence: 99%
“…Similarly, patient survival appeared to rapidly decline particularly in the <8.6 kg weight group in the immediate post‐transplant period. Several other single‐center studies have examined outcomes in children <15 kg 21–24 . Two studies comparing children <15 kg and those ≥15 kg showed that there was no difference in allograft outcomes based on weight at the time of transplant 22,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Several other single-center studies have examined outcomes in children <15 kg. [21][22][23][24] Two studies comparing children <15 kg and those ≥15 kg showed that there was no difference in allograft outcomes based on weight at the time of transplant. 22,24 One study showed that recipients with a weight <15 kg at the time of transplant were associated with an increased occurrence of venous thrombosis.…”
Section: Ta B L Ementioning
confidence: 99%
“…Nevertheless, improvements in surgical methods and the refinement of skills have led to better transplant success rates in this young patient population. [11][12][13] In young children, meticulous management of intravascular volume is crucial both during surgery and in the immediate postoperative phase. Younger age at transplantation may increase the risk of viral infections due to incomplete immunization schedule, or because many infants are seronegative for CMV when they undergo transplantation.…”
mentioning
confidence: 99%
“…Performing KT in infants involves technical difficulties owing to the small size of the recipient's blood vessels, the infant's lower blood pressure, and the significant mismatch in size between the typically adult‐sized donor kidney (which demands a substantial share of the child's heart output) and the small abdominal cavity of the infant. Nevertheless, improvements in surgical methods and the refinement of skills have led to better transplant success rates in this young patient population 11–13 . In young children, meticulous management of intravascular volume is crucial both during surgery and in the immediate postoperative phase.…”
mentioning
confidence: 99%